Taxonomic and functional homogenization of farmland birds along an urbanization gradient in a tropical megacity - Gabriel Marcacci; Catrin Westphal; Arne Wenzel; Varsha Raj; Nils Nölke; Teja Tscharntke; Ingo Grass (Global Change Biology, 2021)
Urbanization is a major driver of land use change and biodiversity decline. While most of the ongoing and future urbanization hotspots are located in the Global South, the impact of urban expansion on agricultural biodiversity and associated functions and services in these regions has widely been neglected. Additionally, most studies assess biodiversity responses at local scale (α‐diversity), however, ecosystem functioning is strongly determined by compositional and functional turnover of communities (β‐diversity) at regional scales. We investigated taxonomic and functional β‐diversity of farmland birds across three seasons on 36 vegetable farms spread along a continuous urbanization gradient in Bangalore, a South Indian megacity. Increasing amount of grey area in the farm surroundings was the dominant driver affecting β‐diversity and resulting in taxonomic and functional homogenization of farmland bird communities. Functional diversity losses were higher than expected from species declines (i.e., urbanization acts as an environmental filter), with particular losses of functionally important groups such as insectivores of crop pests. Moreover, urbanization reduced functional redundancy of bird communities, which may further weaken ecosystems resilience to future perturbations. Our study underscores urbanization as a major driver of taxonomic and functional homogenization of species communities in agricultural systems, potentially threatening crucial ecosystem services for food production.